Integrity and reflections of the past a phenomenographic analysis - Risos Rio, Germina Emily (Florida Florida Atlantica University, 2008)
The graying of America as a sociological and health care phenomenon continues to dictate the demand for creative and innovative interventions that can directly influence the quality of life of nursing home residents. Creative Reminiscence is a program that fosters the active reliving of the past through narration, such as in story-telling, and the use of creative art expression to uncover meaningful life events or valuable life experiences.
The purpose of this study was to investigate and describe the meaningful life events elicited by the experience of Creative Reminiscence using a phenomenographic approach. Existing (archived) data - transcribed interviews, poetry and painting on planters that were obtained from 20 participants of Creative Reminiscence program entitled Le Jardin de Sante - were analyzed.
Five variations of meaningful memories evoked by Creative Reminiscence were identified. These are described as follows: (a) memories that rejuvenate the elder’s sense of connection; (b) memories that revive the elder’s sense of love and intimacy; (c) memories that restore the elder’s sense of being; (d) memories that reassert the elder’s sense of control; and (e) memories that reinstitute the elder’s sense of purpose. In a caring interaction with Creative Reminiscence, the nursed are able to transcend, moving back in time (past) to appreciate segment(s) of their lives, with triumphs and disappointments that give meaning to their inner conflict/human struggle (present), and integrate a sense of confidence and acceptance of their lives to sustain well-being and a sense of wholeness.
This research highlights the similarities and differences in the description of memories by the nursing home residents evoked during Creative Reminiscence. The results of the study support Erikson’s notion of the circular nature of the life cycle, wherein there is an inherent need at the last stage of life to re-integrate ascendant psychosocial themes. Taking into account the meaning that nursing home residents ascribe to their experiences provided data on strategies nurses and caregivers can use effectively to help these elders transcend despair. Further research is recommended using a more diverse sample and in more diverse geographical locations. Current standardized instruments may be revised to quantify effects on the ascendant psychosocial themes.
Dissertation (Doctor of Nursing Science) -- Florida Atlantic University, December 2008.
Bibliography: leaves 92-100.
Keywords: Phenomenographic analysis